Influencia del flujo de marea en la migración de poslarvas de Fartantepenaeus stylirostris en la Boca de Ceuta, Sinaloa, México - Almaral-Mendívil, Alma Rosa; Ordóñez-López, Uriel (Revista de Biología Tropical, 1999)
The variation in density of postlarval Faifantepenaeus styllirostris (bine shrimp) was studied in relation to rising tides, moon phases and tidal stream velocity. The possible relationship between postlarval density and abiotic parameters was also investigated between 1988-1989. Montly net tows of ten minútes durations were conducted at the surface and middle of column water using a conical net 50 cm of diameter and 450 micron mesh. A total of 7552 postlarvae (20.6 postlarvae/m3) were collected. The temporal analysis showed two rises on July (7.8 postlarvae/m3) and September (3.5 postlarvae/m3). Postlarval densífy was no significantly different (ANOVA p> 0.05) among depths or sampling locations in the channel. However, the period of postlarval fluxes were significantly different with a higher migration during flux one relative to tlux two. Postlarval density was significaritly different between full moon (lower density) and new moon (higher density) (ANOVA p<.0.05). Moreover, lhere were positive but not significant relations between the temporal variation in postlarval density and water temperature and current velocity, but was negative with salinity and not significant (Pearson p>.0.05). The 1988-1989 perlod was dominated by lhe presence of cold water masses from the north Pacific. lt is possible that this phenomenon affected reproduction and spawning of the blue shrimp and caused a temporal displacement of lhe peak season of postlarval recruitment into the bay.